2011
DOI: 10.1258/ebm.2011.010287
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 promotes radioresistance of CD44+/CD24−/low cells in breast cancer

Abstract: Breast cancer-initiating cells are a relatively radioresistant subpopulation of breast cancer cells. However, the mechanism of this radioresistance is still unclear. This study aimed to investigate the effect of radiation on the levels of signal transducer and activator of transcription 1 (STAT1) in mammospheres of cancer-initiating cells and monolayer cultures of MCF-7 cells. We isolated CD44(+)/CD24(-/low) cancer-initiating cells from MCF-7 cells and propagated them as mammospheres. Next we used realtime qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…In addition, a link between STAT1 and therapy resistance has been uncovered (Khodarev et al, 2004; Khodarev et al, 2007; Rickardson et al, 2005; Weichselbaum et al, 2008). Interestingly, one report demonstrated that STAT1 signaling contributes to radioresistance in breast cancer-initiating cells (Zhan et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a link between STAT1 and therapy resistance has been uncovered (Khodarev et al, 2004; Khodarev et al, 2007; Rickardson et al, 2005; Weichselbaum et al, 2008). Interestingly, one report demonstrated that STAT1 signaling contributes to radioresistance in breast cancer-initiating cells (Zhan et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these results, suppression of STAT1 by fludarabine led to the radiosensitization of renal cell carcinoma cell lines (21). Zhan and colleagues showed that increased expression of STAT1 promotes radioresistance of breast cancer stem-like cells cultured as mammospheres (22). Frykn€ as and colleagues showed that a myeloma cell line overexpressing STAT1 and ISGs was significantly more radioresistant relative to the parental cell line exhibiting a low expression of STAT1 (23).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…In fact, the ability of these cells to replicate in an in vitro model following at least four generations of xenograft transplanted mice has also suggested their significant role in tumor relapse and metastasis (23). Potential mechanisms of chemotherapy and radiation resistance associated with this phenotype were shown to include the presence of lower concentration of reactive oxygen species, cell dormancy, efficient DNA-repair mechanisms, overexpression of EMT markers, and activation of WNT/β-catenin, Hedgehog and NOTCH signaling pathways and signal transducer and activator of transcription 1 (STAT1) and STAT3 signaling (5,24,(25)(26)(27)(28)(29)(30). As a consequence, the CD44 + /CD24 −/low phenotype in breast cancer is currently being assessed as a therapeutic target.…”
mentioning
confidence: 99%